Semen analysis in the Peruvian Center for Fertility Marriage - Cancino Izaguirre, Heli (2015)
It can not be the study of a couple with infertility problems without analyzing the husband's sperm and is recommended to start with it. Peruvian reviewed 1,006 stories entered Matrimonial Fertility Center between 1969-1973 and found that 1,457 had been made espermatogramas in these patients. Almost half had more of a semen analysis. We prefer obtaining sperm is made by masturbation for a better study of the time mismo.Creemos sexual abstinence for specimen collection must be the same as marriage often has a conjugal relationship study between the two.